Umiejętność korzystania z mediów dzisiaj jako kompetencja społeczna oraz życiowo potrzebna umiejętność osobista: przykład Ukrainy - Harmatiy, Olha (My University, 2019)
Media literacy is examined as actual and practically meaningful personal and social competence. Media literacy is the result of media education the purpose of which is adequate perception and interpretation of media reports, making of skills of analysis and estimation of media content. Ukrainian society needs such abilities, as there is corporate and political control above basic media resources. And in the conditions of challenges of an informatively psychological war media literacy of citizens becomes the important constituent of national security. Media education is characterized as a modern method of forming demand for high-quality mass-media without which democratic society is impossible. Characteristics of critical thinking within the framework of media education are found out. Targets and principles of Conception of introduction of media education in Ukraine are examined.
Media literacy today as a public competence and vital personality skill: a case of Ukraine
Keywords: media literacy; mass media; Ukraine